Transmission of racial prejudice: from parents' cognitive styles, parenting styles and expectations to children's biases - Ng, Ying Ying (Nanyang Technological University, 2022)
Need for closure and authoritarianism are attributes that are robustly linked to racial prejudice in the current literature. However, little is known about how having these attributes as parents would influence children’s racial biases. The present study examined the role of parents’ need for closure (NFC), authoritarian parenting styles and expectations for their child’s interdependent self-concept on children’s implicit and explicit racial bias (N = 97). It was hypothesised that parents’ authoritarian parenting styles would mediate the relationship between parents’ NFC and children’s implicit and explicit racial biases. It was also predicted that parents' expectations for their child’s interdependent self-concept would mediate the relationship between parents’ NFC and children’s implicit and explicit racial biases. Parent- child dyads were recruited by Agency for Science, Technology and Research (A*STAR) as part of Growing Up in Singapore Towards Healthy Outcomes (GUSTO), an on-going longitudinal study. Parents’ NFC was assessed using the Need for Cognitive Closure Scale (NFC-SF), parents’ authoritarian parenting was measured with the Parenting Styles and Dimensions Questionnaire (PSDQ) and parents’ expectations for their child’s interdependent self-concept was evaluated with a reworded version of the Self-Construal Scale when their child was 3, 6, and 8.5 years old respectively. When children were 10.5 years old, their implicit racial bias was measured by the Implicit Association Task while their explicit racial bias was assessed with the explicit racial bias task. While the hypotheses were not supported, significant implicit and explicit racial biases were found among 10.5 years old children. The findings also revealed that the Chinese children demonstrated significantly higher levels of implicit and explicit racial bias than their Malay and Indian counterparts. Together, the findings provide insights on ethnic differences in the development of children’s racial biases.